2012
DOI: 10.17221/5256-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of the giant liver fluke (Fascioloides magna) in the Czech Republic and potential risk of its further spread

Abstract:   The giant liver fluke, Fascioloides magna, is of interest to wild-life managers, veterinarians and researchers, due to its unusual body size (3–10 cm), high pathogenic potential and because it is continuously spreading to new areas, especially in Europe. Annually, the number of cases of animal infections (mainly cervids and bovids) caused by this fluke is monitored in many European countries, including the Czech Republic (with some foci of prevalence over 90%). During the years 2009 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Molecular studies have shown that the Czech fluke haplotype is convergent with that found in other Danube countries, suggesting the parasite was transported from the Czech Republic to Hungary, Austria, and Croatia (9,20). Further studies in the Czech Republic have shown the spread of F. magna foci not only in the south-western parts of the country but also in the west, near the German border and in the north, near the Polish border (7). Recent molecular research on giant liver fluke specimens from southwestern Poland based on mitochondrial markers (cox1 and nad1) revealed the genetic uniformity of F. magna specimens from Poland with certain specimens from a Czech natural focus (8).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Molecular studies have shown that the Czech fluke haplotype is convergent with that found in other Danube countries, suggesting the parasite was transported from the Czech Republic to Hungary, Austria, and Croatia (9,20). Further studies in the Czech Republic have shown the spread of F. magna foci not only in the south-western parts of the country but also in the west, near the German border and in the north, near the Polish border (7). Recent molecular research on giant liver fluke specimens from southwestern Poland based on mitochondrial markers (cox1 and nad1) revealed the genetic uniformity of F. magna specimens from Poland with certain specimens from a Czech natural focus (8).…”
Section: Discussionmentioning
confidence: 83%
“…There has been an increase in the number of infections by this parasite in Central Europe in recent years. The giant liver fluke has established three permanent natural foci: La Mandria Regional Park in northern Italy, the Danube floodplain forests, including Austria, Slovakia, Hungary, Croatia, and Serbia, and lastly the Czech Republic and southwestern Poland (7,11,12,15,18,22). F. magna was first noted in red deer in Poland by Salomon in 1932 (19), followed by Ślusarski in 1953 (21).…”
Section: Introductionmentioning
confidence: 99%
“…Within 10 yr, extensive fluke-related mortality of elk occurred and outbreaks continue (Balbo et al 1987). Molecular evaluation confirmed multiple introductions of F. magna into Europe from translocated elk and white-tailed deer (Odocoileus virginianus) (Kralova-Hromadova et al 2011), and the distribution continues to expand (Novobilský et al 2007;Rajkovic-Janje et al 2008;Kasny et al 2012). …”
Section: Introductionmentioning
confidence: 84%
“…Giant liver flukes apparently contribute to mortality of heavily infected individuals (Kermode 1916;Fenstermacher and Olsen 1942;Cheatum 1951;Murray et al 2006) and are a serious concern for wildlife managers in North America (Pybus 2001) and Europe (Kasny et al 2012). We examined the interplay of giant liver fluke among sympatric, free-ranging ungulates in various habitats within Banff and Kootenay national parks in the Rocky Mountains of AB and BC (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of this parasite in the fallow deer population represents a threat as the giant liver fluke could spread to domestic ruminants which reside in close proximity to hunting grounds [1,4,5,7-9]. …”
Section: Discussionmentioning
confidence: 99%